EFEK KENAIKAN SUHU DAPUR INDUKSI ELEKTROMAGNETIK ALTERNATOR TERHADAP PERUBAHAN RESISTANSI LILITAN STATOR - Parlindungan Pandapotan Marpaung (Politeknik Negeri Jakarta, 2022)
In this study, the design of the ac power plant equipment using an alternator derived from a motorcycle was carried out to produce an ac output voltage in the stator coil winding based on the electromagnetic induction process. The problem is that the ac output voltage flows rotary current or eddy current through the coil windings causing heat in the core plane which is in the alternator electromagnetic induction furnace. The initial condition of the electromagnetic induction alternator temperature is Tind(awal) = 30 oC, coil resistance Rt(awal) = 1.28 ohms and ac output voltage Vo(awal) = 12.68 volts. The research method was carried out by increasing the Tind parameter initial causing the effect of increasing the resistance of the conductor coil winding material as the output voltage decreased. The specification of the temperature coefficient of the coil conducting conductor is 0.0291 oC-1 the temperature increase of the electromagnetic induction alternator is Tind. 62 oC causes the effect of increasing the coil resistance as the output voltage decreases to Vo(temp.) = 7.68 volts ac. This decrease in the ac output voltage of the alternator causes the electricity supply to the automotive electrical load to become ineffective and inefficient. Keywords: alternator ; electromagnetic induction ; coil windin ; temperature coefficient ; initial conditions